ANALYSIS AND EVALUATION OF LEGAL AID IN THE INDONESIAN COURT - Suhariyanto, Budi; Mustafa, Cecep (Jurnal Hukum dan Peradilan, 2022)
This article examines the regulation and application of legal aid services in Indonesian Courts. Normatively, the guidelines for the provision of legal aid in court are based on the Law on Judicial Power, Law on General Courts, Law on Religious Courts and Law on State Administrative Courts, and Supreme Court Regulation Number 1 the year 2014 (Perma). On the one hand, there is incoherence in the provision where the law determines that free legal service (Posbakum) service supported any level of the court until the decision is legally binding and executable, whereas in Perma applicable for the district court. On the other hand, there is an expansion of the provision of legal aid services regulated by Perma, namely that the recipient of services is not required by the poor as stipulated by law, but also for those who cannot afford to pay for advocate services. The leniency of this requirement is to facilitate people who are not categorized as poor but cannot pay for the services of a lawyer. In addition, Perma also provides services in the form of Sessions Outside the Court Building (SLGP) to facilitate justice seekers who have limited access to transportation and accommodation for the distance from the court. So the inability of the justice-seeking community is also interpreted as the inability to access trials or litigate cases in court due to the remote location or difficulty in transportation and accommodation. There are several obstacles in providing legal aid services at the court, namely related to budget constraints, lack of socialization, and availability of facilities and infrastructure. This article contributes to the role of the Indonesian Court in providing unique access to justice.